2012
DOI: 10.1063/1.4730392
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic states and optical properties of single-layer carbon-doped hexagonal boron nitride

Abstract: We show that carbon-doped hexagonal boron nitride (h-BN) has extraordinary properties with many possible applications. We demonstrate that the substitution-induced impurity states, associated with carbon atoms, and their interactions dictate the electronic structure and properties of C-doped h-BN. Furthermore, we show that stacking of localized impurity states in small C clusters embedded in h-BN forms a set of discrete energy levels in the wide gap of h-BN. The electronic structures of these C clusters have a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 38 publications
(44 reference statements)
6
65
1
Order By: Relevance
“…The doping states of C atoms embedded in h‐BN will be localized in the vicinity of C atoms and extend into the insulating h‐BN area. The carbon atoms substituting boron atoms give rise to an unpaired electron and induce a local magnetic moment ( Figure a) . Constructing custom‐designed C doped h‐BN via interaction of CO molecules with vacancy defects in h‐BN has been demonstrated theoretically .…”
Section: Synthesis Properties and Applications Of Two Dimensional H‐bnmentioning
confidence: 99%
“…The doping states of C atoms embedded in h‐BN will be localized in the vicinity of C atoms and extend into the insulating h‐BN area. The carbon atoms substituting boron atoms give rise to an unpaired electron and induce a local magnetic moment ( Figure a) . Constructing custom‐designed C doped h‐BN via interaction of CO molecules with vacancy defects in h‐BN has been demonstrated theoretically .…”
Section: Synthesis Properties and Applications Of Two Dimensional H‐bnmentioning
confidence: 99%
“…[72] We obtain this energy as the energy difference between the total energy of spin-polarised ground states and that of the non-spin-polarised (non-magnetic) system. [47] In the case of C B , Park et al [71] reported that the impurity state associated with C is located close to the conduction band. We observe a metallic behaviour in the majority spin channel with the Fermi level lying on the impurity states, while the minority spin component shows a semiconducting behaviour.…”
Section: Fig 3 Andmentioning
confidence: 99%
“…Different patterned C-doping might limit the half-metallicity in C-doped h-BN systems. [28] Furthermore, we considered passivation defects by 9.375 %B -doping at the Ns ite of h-BN. The calculated formation energy (6.94 eV per dopant) is significantly higher than for C-doping (0.86 eV per dopant)a tt he Bs ite of h-BN.…”
Section: C@h-bnmentioning
confidence: 99%
“…Conversely,c arbon doping might be an effective strategy to inducef erromagnetism and half-metallicity in BN-based systems. [25][26][27][28][29][30][31][32][33] In 2005, Wue tal. [29] demonstrated that C-doping at Ba nd Ns ites of BN nanotubes spontaneously induces magnetisation.S ubsequently,Z hou et al [30] establishedt hat C-doping in the open arm-chair( one end of the nanotube is functionalised with H, whereas the other end is open) BN nanotube leads to spin-splitting.…”
Section: Introductionmentioning
confidence: 99%